Discovering the music of Latin America [videorecording] - Wilets, Bernard (Encyclopedia Britannica Educational Corporation [producer], 1982)
Explains how the traditions of all these various civilizations combined to create a distinctive form of music that is popular throughout the world. Traces the origins of the regions different musical instruments as well as the styles and steps of a range of Latin American dances, including the flamenco, the tango, the rhumba and the bossa nova.